2018
DOI: 10.1186/s12859-018-2386-9
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning architectures for prediction of nucleosome positioning from sequences data

Abstract: BackgroundNucleosomes are DNA-histone complex, each wrapping about 150 pairs of double-stranded DNA. Their function is fundamental for one of the primary functions of Chromatin i.e. packing the DNA into the nucleus of the Eukaryote cells. Several biological studies have shown that the nucleosome positioning influences the regulation of cell type-specific gene activities. Moreover, computational studies have shown evidence of sequence specificity concerning the DNA fragment wrapped into nucleosomes, clearly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…The output of the network is calculated by using the following equation: where the symbol ⊙ indicates the multiplication element by element. In a preceding work [ 26 ] we found that substituting a convolutional layer with an LSTM layer can improve the performance in sequence classification tasks, and the resulting network is in Fig. 3 .…”
Section: Methodsmentioning
confidence: 89%
See 4 more Smart Citations
“…The output of the network is calculated by using the following equation: where the symbol ⊙ indicates the multiplication element by element. In a preceding work [ 26 ] we found that substituting a convolutional layer with an LSTM layer can improve the performance in sequence classification tasks, and the resulting network is in Fig. 3 .…”
Section: Methodsmentioning
confidence: 89%
“…We also calculated the Roc Curve to compare the prediction performance of the four methods and we reported the Area Under the Curve (AUC). The first set of results is related to the HS, DM, E and Y datasets, and in Table 4 the results obtained from two models used in our recent works, indicated as simple LSTM [ 26 ] and ConvNet [ 27 ] are reported, together with the CORENup and the LeNup networks. The two simpler networks have almost always worst performance than the more complex networks, confirming that with more parameters it is possible to improve the performance of the classifier.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations